The high-mass end of the red sequence at z ∼ 0.55 from SDSS-III/BOSS: completeness, bimodality and luminosity function. Issue 2 (9th June 2016) - Montero-Dorta, Antonio D.; Bolton, Adam S.; Brownstein, Joel R.; Swanson, Molly; Dawson, Kyle; Prada, Francisco; Eisenstein, Daniel; Maraston, Claudia; Thomas, Daniel; Comparat, Johan; Chuang, Chia-Hsun; McBride, Cameron K.; et al.
Abstract: We have developed an analytical method based on forward-modelling techniques to characterize the high-mass end of the red sequence (RS) galaxy population at redshift z ∼ 0.55, from the DR10 BOSS (Baryon Oscillation Spectroscopic Survey) CMASS spectroscopic sample, which comprises ∼600 000 galaxies. The method, which follows an unbinned maximum likelihood approach, allows the deconvolution of the intrinsic CMASS colour–colour–magnitude distributions from photometric errors and selection effects. This procedure requires modelling the covariance matrix for the i -band magnitude, g − r colour and r − i colour using Stripe 82 multi-epoch data. Our results indicate that the error-deconvolved intrinsic RS distribution is consistent, within the photometric uncertainties, with a single point (<0.05 mag) in the colour–colour plane at fixed magnitude, for a narrow redshift slice. We have computed the high-mass end ( 0.55 M i ≲ −22) of the 0.55 i -band RS luminosity function (RS LF) in several redshift slices within the redshift range 0.52 < z < 0.63. In this narrow redshift range, the evolution of the RS LF is consistent, within the uncertainties in the modelling, with a passively evolving model with Φ* = (7.248 ± 0.204) × 10 − 4  Mpc −3  mag −1, fading at a rate of 1.5 ± 0.4 mag per unit redshift. We report RS completeness as a function of magnitude and redshift in the CMASS sample, which will facilitate a variety of galaxy-evolution and clustering studies using BOSS. Our forward-modelling method lays the foundations for future studies using other dark-energy surveys like the Extended Baryon Oscillation Spectroscopic Survey or the Dark Energy Spectroscopic Instrument, which are affected by the same type of photometric blurring/selection effects.